Economic Benefit of Tuberculosis Control - Laxminarayan, Ramanan; Klein, Eili; Dye, Christopher; Floyd, Katherine; Darley, Sarah; Adeyi, Olusoji (World Bank, Washington, DC, 2012)
Tuberculosis is the most important infectious cause of adult deaths after HIV/AIDS in low- and middle-income countries. This paper evaluates the economic benefits of extending the World Health Organization's DOTS Strategy (a multi-component approach that includes directly observed treatment, short course chemotherapy and several other components) as proposed in the Global Plan to Stop TB, 2006-2015. The authors use a model-based approach that combines epidemiological projections of averted mortality and economic benefits measured using value of statistical life for the Sub-Saharan Africa region and the 22 high-burden, tuberculosis-endemic countries in the world. The analysis finds that the economic benefits between 2006 and 2015 of sustaining DOTS at current levels relative to having no DOTS coverage are significantly greater than the costs in the 22 high-burden, tuberculosis-endemic countries and the Africa region. The marginal benefits of implementing the Global Plan to Stop TB relative to a no-DOTS scenario exceed the marginal costs by a factor of 15 in the 22 high-burden endemic countries, a factor of 9 (95% CI, 8-9) in the Africa region, and a factor of 9 (95% CI, 9-10) in the nine high-burden African countries. Uncertainty analysis shows that benefit-cost ratios of the Global Plan strategy relative to sustained DOTS were unambiguously greater than one in all nine high-burden countries in Africa and in Afghanistan, Pakistan, and Russia. Although HIV curtails the effect of the tuberculosis programs by lowering the life expectancy of those receiving treatment, the benefits of the Global Plan are greatest in African countries with high levels of HIV.